Strategi Pengembangan Sumber Daya Manusia dalam Meningkatkan Kinerja Karyawan di PT. Sawit Jujuhan Abadi Sirih Sekapur, Kec. Jujuhan, Kabupaten Bungo, Jambi - Aulia Nita Putri; Harfandi Harfandi (ARZUSIN, 2026)
Human resource development strategies have become a focus in various previous studies; however, research that specifically discusses the gap between labor needs and the availability of competent human resources in the palm oil plantation industry remains limited. This study aims to analyze human resource development strategies in improving employee performance at PT Sawit Jujuhan Abadi. This study employed a qualitative approach with a case study design. The research informants consisted of personnel division representatives and four employees selected through the purposive sampling technique. Data were collected through observation, interviews, and documentation and were then analyzed using interactive qualitative analysis and SWOT analysis through the IFE and EFE matrices. The results show a competency gap between the company’s needs and the workforce’s capabilities, which affects work effectiveness and the achievement of production targets. The company has implemented various human resource development strategies, such as training, improvement of technical skills, collaboration with external institutions, and the application of industry standards to improve employee performance. These findings contribute to the development of human resource management studies and broaden understanding of workforce management in the palm oil plantation industry. The conclusion of the study emphasizes that competency alignment is an important factor in improving employee performance. The practical implication is that the company needs to continuously optimize human resource development strategies to improve workforce quality, effectiveness, and productivity.